Escolarização básica na EJA: ensino-aprendizagem e desenvolvimento de jovens e adultos trabalhadores - Silva, Gabriel de Nascimento e (2022)
Youth and Adult Education (EJA) is a form of basic schooling, aimed at those students who didn’t have access or conditions to continue their studies at the expected age, especially workers. The late return to school and the condition of student-worker demand new readings on the teaching-learning processes, because it occurs in a period of development where the work activities figure as more significant in the student's life, thus requiring special attention to the organization of the pedagogical activity. In this perspective, this research tried to reveal the contributions of the Cultural-Historical Psychology for the EJA field as well as to analyse the organisation of the pedagogical practices in this modality. The methodological strategies adopted were: integrative review of Brazilian dissertations and thesis that investigate the EJA in the light of the Cultural-Historical Psychology and the accomplishment of semi-structured interviews with three teachers acting in the modality of EJA. The analyses undertaken are based on the Cultural-Historical Psychology, in its Historical-Dialectical Materialist base, especially regarding the periodization of the human development and its implications to the teaching organization. We observed, with the review, the recentness of this discussion and disperse production. The themes approached were: senses and meanings attributed to schooling; teaching practices and pedagogical resources used; educational policies; and, development of the higher psychological functions. With the interviews, we evidenced the insufficient appropriation of the theories of development and adult learning, resulting from a teaching training that neglects the study about EJA, resulting in incoherent pedagogical practices. Thus, we conclude that the teaching-learning process in EJA mediated by study and work activities remains little explored and lacking propositions. We defend that the knowledge about the cultural-historical periodization logic of development, especially the understanding of work as the main activity in adulthood, may contribute to the planning and organization of the pedagogical activity in EJA.